Bibliotherapy Outcomes In Preschoolers With Infectious Diseases: A Two-Site Comparison Of Dengue Hemoragic Fever And Acute Respiratory Infection Cases - Pangesti, Nova Ari (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2026)
ABSTRACTBackground: Hospitalization in preschool children, especially due to infectious diseases such as Dengue Haemorrhagic Fever (DHF) and Acute Respiratory Tract Infection (ARI), frequently triggers anxiety that affects psychological well-being and the recovery process. Bibliotherapy, a non-pharmacological intervention using age-appropriate picture storybooks, has been applied to reduce anxiety. However, its effectiveness may differ depending on the illness and individual response. Research Objective: To compare the effectiveness of bibliotherapy in reducing anxiety levels among hospitalized preschool children with DHF and ARI. Methods: This comparative case study with a qualitative approach involved four children aged 4–7 years: two diagnosed with DHF at Dr. Soedirman General Hospital, Kebumen, and two diagnosed with ARI at Majenang General Hospital. Bibliotherapy sessions were conducted for three consecutive days, one 20-minute session per day, using picture storybooks. Anxiety levels were assessed through behavioral observation and the Spence Children’s Anxiety Scale (SCAS) Parent Report. Results: The findings showed differences between the two groups. Children with DHF demonstrated a more significant reduction in anxiety within the first two days, whereas children with ARI showed a slower decrease, with improvements observed on days two and three. Moreover, children with DHF exhibited positive emotional expressions earlier than those with ARI. Conclusion: Bibliotherapy appears to be more effective in reducing anxiety levels more rapidly in preschool children hospitalized with DHF compared to those with ARI.ABSTRAK                                                              ABSTRAKLatar Belakang: Hospitalisasi pada anak prasekolah, khususnya akibat penyakit infeksi seperti Dengue Hemorrhagic Fever (DHF) dan Infeksi Saluran Pernapasan Akut (ISPA), sering menimbulkan ansietas yang berdampak pada kondisi psikologis dan proses penyembuhan anak. Biblioterapi salah satu intervensi non-farmakologis yang digunakan untuk mengurangi ansietas melalui media buku cerita bergambar yang sesuai dengan usia. Namun, efektivitas intervensi ini dapat bervariasi tergantung pada kondisi penyakit dan respon individu. Tujuan Penelitian: membandingkan efektivitas biblioterapi dalam menurunkan tingkat ansietas pada anak prasekolah yang menjalani hospitalisasi akibat DHF dan ISPA di dua rumah sakit berbeda. Metode: Penelitian ini menggunakan desain studi kasus komparatif dengan pendekatan kualitatif. Empat anak usia 4–7 tahun yang menjalani perawatan inap menjadi partisipan: dua anak dengan DHF di RSUD Dr. Soedirman Kebumen, dan dua anak dengan ISPA di RSUD Majenang. Intervensi biblioterapi diberikan selama 3 hari berturut-turut, satu sesi per hari selama 20 menit dengan membacakan buku cerita bergambar. Tingkat ansietas diukur melalui observasi perilaku dan kuesioner Spence Children’s Anxiety Scale (SCAS) Parent Report. Hasil: terdapat perbedaan respons dantara dua kelompok anak dengan DHF menunjukkan penurunan skor ansietas yang lebih signifikan dalam dua hari pertama, sedangkan pada anak dengan ISPA, perubahan ansietas terjadi lebih lambat, yakni pada hari ke-2 dan ke-3. Selain itu, anak dengan DHF tampak menunjukkan ekspresi emosional positif lebih cepat dibandingkan anak dengan ISPA. Kesimpulan: Biblioterapi memiliki efektivitas cenderung lebih cepat menurunkan Tingkat ansietas pada anak dengan DHF dibandingkan anak yang mengalami ISPA.